Pengaruh Kepemimpinan, Kompensasi dan Laba pada Kepuasan Kerja Karyawan PT. Bank Bukopin Tbk. Cabang Denpasar - Utama, Made Dwi Pradipta; Ratna Sari, Maria M. (E-Jurnal Akuntansi, 2019)
Job satisfaction is an individual positive attitude in general towards his/her job. In order for the employee to have high job satisfaction, an organization needs to take attention factors which influencing job satisfaction. The research aims to find out the impact of leadership and compensation towards employee’s job satisfaction. In addition also to find out the bigger or stronger impact from both variables towards employee’s job satisfaction. The research was conducted at PT. Bank Bukopin (Persero) Tbk. branch of Denpasar. Amount of sample taken was 89 employees with data collection method was carried out by using questionnaire. Keywords : Impact of Leadership, Compensation, Profit, Job Satisfaction.